1998
DOI: 10.1128/iai.66.11.5337-5343.1998
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of Aortic and Heart Endothelial Cells by Porphyromonas gingivalis

Abstract: Invasion of host cells is believed to be an important strategy utilized by a number of pathogens, which affords them protection from the host immune system. The connective tissues of the periodontium are extremely well vascularized, which allows invading microorganisms, such as the periodontal pathogen Porphyromonas gingivalis, to readily enter the bloodstream. However, the ability of P. gingivalis to actively invade endothelial cells has not been previously examined. In this study, we demonstrate that P. ging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
200
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(216 citation statements)
references
References 33 publications
8
200
0
4
Order By: Relevance
“…In this study, we reported that PAR-4 is strongly expressed on resting T cells; therefore, cleavage and activation of PAR-4 by RgpA could be an important early event. Findings from the present study support this contention: (1) PAR-1, -2 and -4 expression on the cell surface was up-regulated by RgpA; (2) up-regulation of CD69 on T cells by gingipain alone was inhibited by blocking peptide against PAR-2. These results indicating the capacity of RgpA to activate PAR-2 on T cells are in agreement with previous reports [25,26] that PAR-2 plays a crucial role in the local inflammatory reaction within the pathological periodontal pocket.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, we reported that PAR-4 is strongly expressed on resting T cells; therefore, cleavage and activation of PAR-4 by RgpA could be an important early event. Findings from the present study support this contention: (1) PAR-1, -2 and -4 expression on the cell surface was up-regulated by RgpA; (2) up-regulation of CD69 on T cells by gingipain alone was inhibited by blocking peptide against PAR-2. These results indicating the capacity of RgpA to activate PAR-2 on T cells are in agreement with previous reports [25,26] that PAR-2 plays a crucial role in the local inflammatory reaction within the pathological periodontal pocket.…”
Section: Discussionsupporting
confidence: 83%
“…The ability of microbial pathogens, such as P. gingivalis and C. pneumoniae, to potentiate atherosclerosis by establishment of an inflammatory state within the endothelium, is receiving increased attention. Previous reports have established that bacterial infection of endothelial cells stimulates inflammatory markers such as tissue factor, IL-6, chemokines and CAMs (Fryer et al, 1997;Deshpande et al, 1998;Molestina et al, 1998;Dechend et al, 1999;Khlgatian et al, 2002). In this study, we have utilized a series of P. gingivalis fimbria mutants to demonstrate that the expression of 41 kDa (major) fimbria is required for efficient invasion of HAEC.…”
Section: Discussionmentioning
confidence: 90%
“…Invasion of HAEC cells by P. gingivalis strains was quantified by determining the number of cfu following infection at a multiplicity of infection (moi) of 100. HAEC cells were incubated with P. gingivalis strains for 1, 2 and 6 h followed by treatment with metronidazole for killing of adherent external bacteria as previously described (Deshpande et al, 1998). For 'enhanced rate of infection' assays only, bacteria were centrifuged onto HAEC monolayers (350 g for 5 min) as described (Walter et al, 2004).…”
Section: Invasion Of Haec By P Gingivalis Fimbrial Mutantsmentioning
confidence: 99%
“…On the other hand, the inhibitory effects of MCD could not be attributed to its ability to suppress P. gingivalis phagocytosis. Indeed, pretreatment with cytochalasin D, which prevents phagocytosis by blocking actin polymerization (Deshpande et al, 1998), had no significant influence on P. gingivalis-induced cell activation (Fig. 5).…”
Section: Cholesterol Depletion Inhibits P Gingivalis-induced Cytokinmentioning
confidence: 95%
“…Quantification of the degree of colocalization under the different experimental conditions examined revealed that P. gingivalis was about five times less likely to colocalize with lipid rafts in cholesterol-depleted cells than in untreated or cholesterol-reconstituted cells (Table 1). Although cytochalasin D is known to inhibit phagocytosis (Deshpande et al, 1998), it had no effect on the ability of P. gingivalis to colocalize with lipid rafts ( Fig. 2D and Table 1).…”
Section: Cholesterol-dependent Colocalization Of P Gingivalis With Lmentioning
confidence: 98%